Pengaruh Jenis Pahat Terhadap Nilai Kekasaran Permukaan Material Baja Carbon S45C - Maryanti, Budha; Rezaldy, Rezaldy; Joni Pasau, Fransye (Indonesian Society of Applied Science, 2025)
In the turning process, the surface finish of a workpiece can influence the level of visual quality of a workpiece. CNC machine cutting parameters include feed speed, feed depth, and cutting speed. The aim of this research is to determine the effect of carbide insert tool types ZCC WNMG 060408 – DM and VBMT 160408 – HM on the average roughness value in the turning process with a rotational speed of 500 rpm and feed speed variations of 0.10 mm/rev, 0.15 mm/ rev and 0.20 mm/rev on S45C steel material. This research is located at PT. Bin Smeer Jaya with the research sample, namely S45C steel material. This research will be carried out with 3 samples of surface roughness testing each with varying feeding, where the turning process will be carried out on a CNC lathe machine first using ZCC WNMG 060408 – DM and VBMT 160408 – HM carbide insert chisels. The desired roughness standard is 1.8 µm – 2.2 µm. Based on the results of testing the surface roughness value of S45C steel material, the data obtained using the Handysurf E-35 surface roughness measurement tool, the roughness value using the ZCC WNMG 060408 – DM specimen 3 feeding 0.20 mm/rev carbide insert chisel was 2.38 µm, whereas for specimen 3 feeding 0.10 mm/rev is 4.11 µm. Then for the VBMT 160408 – HM carbide insert chisel, specimen 1 feeding 0.10 mm/rev is 1.48 µm, while for specimen 2 feeding 0.20 mm/rev it is 4.41 µm. So it can be concluded that the lowest roughness value occurs in the VBMT 160408 – HM carbide insert chisel compared to the ZCC WNMG 060408 – DM carbide insert chisel type. Therefore, the best level of surface roughness results occurs in the VBMT 160408 – HM carbide insert with the desired roughness standard and optimal visual quality